Seizure rates under treatment with antipsychotic drugs: Data from the AMSP project - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Engel, Rolf R.; Neyazi, Alexandra; Stuebner, Susanne; Toto, Sermin (World Journal of Biological Psychiatry, 2019)
Objectives: The study aimed to assess seizure rates related to different antipsychotic drugs (APDs) in a clinical setting using data from the drug safety programme Arzneimittelsicherheit in der Psychiatrie (AMSP). Methods: Psychotropic drug use data and reports of APD-related seizures were collected in 89 psychiatric hospitals in Austria, Germany and Switzerland from 1993 to 2015. Results: Of 475,096 patients under surveillance, 320,383 patients were treated with APDs for the main indications of schizophrenic disorders, mood disorders and organic disorders. A total of 144 APD-related tonic clonic seizures were identified (0.04%). The butyrophenones ranked slightly lower (0.03%) compared to the phenothiazines, thioxanthenes and second-generation APDs (0.05% each). No significant differences were observed when comparing first- and second-generation APDs. Clozapine was related to the highest seizure rate (0.18%). In 107 cases (74.3%), more than one drug was considered responsible for seizure induction. With the exception of clozapine, seizures imputed to a single APD were in the clear minority. Seizure rates under the combinations of APDs with tricyclic antidepressants or lithium, as well as under triple combinations of APDs, were increased approximately two-fold. Young age (<= 30 years), the male gender, and diagnosis of schizophrenic disorder were associated with significantly higher seizure rates (P < 0.05). Conclusions: Closely reflecting daily clinical practice, the present results provide supplementary information regarding APD therapy for patients not only at risk for seizures but also seizure-unaffected psychiatric inpatients.
CRIS-Team WoS Importer:2020-02-11